Towards Equitable Healthcare: Redesigning Informed Consent Regulations - Masyuri, Rohmad Imam; Setioboedi, Didiet; Mashdurohatun, Anis; Kadarmo, Dhiwangkoro Aji; Fareha, Nur (Journal of Ecohumanism, 2024)
Informed consent is a fundamental element of ethical and legal healthcare practices, serving as a cornerstone for patient autonomy and equitable care. In Indonesia, informed consent is regulated under frameworks such as Law No. 17 of 2023 on Health, Government Regulation No. 28 of 2024, and Ministerial Regulation No. 290 of 2008. While these regulations establish foundational guidelines, they are limited in addressing contemporary challenges, particularly in the communication of medical information tailored to diverse patient needs. This article examines the gaps in the current regulatory framework, particularly regarding the inadequacies in ensuring patient understanding and participation in medical decision-making. The analysis highlights key shortcomings, including the lack of detailed technical provisions for adapting information delivery to various patient conditions, such as those with disabilities, language barriers, or limited literacy. It argues that these gaps undermine the principles of equity and justice, potentially resulting in consent that does not reflect informed patient choice. To address these challenges, the article proposes regulatory reconstructions emphasizing justice, transparency, and inclusivity. Suggested reforms include the mandatory use of digital documentation, enhanced communication technologies, and support systems such as translators or visual aids for vulnerable populations. By integrating these reforms into the legal framework, the healthcare system can foster a more inclusive informed consent process, enhancing patient trust, autonomy, and equity in medical decision-making. These changes are crucial for bridging the gap between ethical theory and practical application in Indonesia’s evolving healthcare landscape.